(untitled) (Journal of actual problems of jurisprudence, 2019)
Historical forms of socialization and solidarity of the population of different countries, nations, regional population can be monotonous. One of these forms of social solidarity are the local authorities, many of the crucial issues of local importance. Historically, this form existed among the ancient Kyrgyz people and the same form is preserved by the Constitution and now needs the support of the state. Kyrgyz identity model of local self-government has its reasons related to national traditions, customs Kyrgyz and Kazakhs trust, mutual respect, democratic relations, etc. Key words: local government, social solidarity, the government, the legal self-fulfillment, social management, statehood.